ENTREPRENEURIAL CULTURE, INNOVATION, AND DIGITAL MARKETING CAPABILITY IN MSMEs’ SUSTAINABLE COMPETITIVE PERFORMANCE - Eriyani Eriyani; Inaya Sari Melati; Lola Kurnia Pitaloka; Rusdarti (EDUCATIONE, 2026)
Micro, small, and medium enterprises (MSMEs) require complementary organizational and digital capabilities to maintain competitiveness in increasingly dynamic markets. This study examines the effects of entrepreneurial culture and innovation on sustainable competitive performance and evaluates the direct and moderating role of digital marketing capability. A quantitative survey was administered to 136 owners or managers of processing-sector MSMEs in Semarang Regency, Indonesia. Data were analyzed using partial least squares structural equation modeling with 5,000 bootstrap resamples. Digital marketing capability had a strong positive effect on sustainable competitive performance (β = 0.602, p < .001), and innovation also had a positive effect (β = 0.218, p = .048). Entrepreneurial culture did not have a significant direct effect (β = −0.033, p = .604). Digital marketing capability negatively moderated the relationship between entrepreneurial culture and performance (β = −0.215, p = .002), indicating that entrepreneurial values may become less effective when they are not aligned with data-informed digital practices. Its positive moderation of the innovation–performance relationship did not reach the 5% significance level (β = 0.147, p = .056). The findings show that sustainable competitiveness depends more directly on actionable innovation and well-developed digital marketing capability than on entrepreneurial values alone. MSME support programs should therefore integrate product and process innovation with practical digital marketing, analytics, and managerial execution.